A systematic review and meta-analysis of the effectiveness of perineural dextrose injection in peripheral compression neuropathies of the upper limbs - Fatemeh Azizi; Faezeh Saber Gharesoo; Fereshteh Eidy; Sama Heidari; Nastaran Maghbouli; Shirin Djalalinia; Amir Kasaeian (Heliyon)
Background: Entrapment neuropathies, marked by nerve compression at various anatomical sites, can be effectively managed using conservative approaches like injections. Dextrose 5 % water injection has emerged as a potential therapy by reducing inflammation and promoting tissue regeneration. We aimed to evaluate dextrose injection's efficacy in treating entrapment neuropathies in upper extremities. Method: We systematically searched EMBASE, Scopus, Web of Science, and PubMed. Our eligibility criteria included participants aged 18 and older who had peripheral upper limb nerve entrapment from non-metabolic and non-traumatic sources. These participants were treated with dextrose injection compared to those receiving other injectables, such as corticosteroids and non-corticosteroid medications. The primary outcome was pain, with secondary outcomes including function, ultrasonographic, and electrodiagnostic findings. The quality of the clinical trials was assessed using Cochrane tools. Random-effect model was employed for meta-analysis. Results: Thirteen studies, involving 754 patients, were included, with only two showing serious bias risk. Initial findings indicate significant pain relief with dextrose injection within a short time (≤4 weeks) compared to normal saline (MD: −1.30, 95%CI: −2.12; −0.47). Dextrose also demonstrated a significant pain decrease compared to corticosteroids (MD: −0.81, 95 % CI: −1.40; −0.21) with low heterogeneity (I2 = 9 %, P = 0.36), and significantly improved function (MD = −0.46, 95 % CI: −0.76; −0.16) with low heterogeneity (I2 = 17 %, P = 0.31) in mid-term (one to six months). Conclusion: This meta-analysis suggests dextrose injection as an effective therapy for managing pain and restoring function in entrapment neuropathies. However, further high-quality studies are needed to confirm these findings and establish optimal dosing regimens and injection protocols. Healthcare providers should consider integrating dextrose injection into their treatment strategies for patients with entrapment neuropathies.